2x - 2y = -2
x - 4y = 5
In x -4y =5, add 4y to both sides to get x = 4y +5
Now substitute that equation for x in the first equation:
2x - 2y = -2
2(4y +5) - 2y = -2
Simplify:
8y +10 - 2y = -2
Combine like terms:
6y +10 = -2
Subtract 10 from both sides:
6y = -12
Divide both sides by 6:
y = -12 /6
y = -2
Now you have y, substitute y in the second equation to solve for x:
x - 4y = 5
x -4(-2) = 5
Simplify:
x+8 = 5
Subtract 8 from both sides:
x = -3
Now you have x = -3 and y = -2
The answer is (-3,-2)